PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN - Roidah Lina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Building an organization is not easy, it requires sufficient resources, especially humans. Employees are the company's most important assets, hence all organizational activities are carried out. Therefore, prepare it from the beginning (recruitment). The purpose of this study was to determine the effect of recruitment on employee performance. The research design used is quantitative and linear regression analysis, with a total sample of 50 and using saturated sample techniques. Furthermore, the study was tested with the stages of analysis that included a descriptive analysis of the questionnaire, a validity test, a reliability test, a linear regression test, a correlation coefficient test and a coefficient of determination test. The results of the regression analysis prove, recruitment has a positive and significant effect on the performance of employees of PT. Tata Sentosa with a regression coefficient of 0.703 and tcount of 8.001. This finding proves that performance can be explained by the recruitment variable. The better the recruitment system implemented will improve employee performance